Incorporating Financial Literacy into the Secondary School Accounting Curriculum: A New Zealand Perspective - Grant Samkin; Mary Low; Jordan Taylor (Australasian Accounting, Business and Finance Journal, 2012)
This paper examines whether selected stakeholder groups believe accounting should continue to be taught as an elective subject in its current form at New Zealand secondary schools or whether incorporating a financial literacy component would increase the subject’s relevance to students. A mixed method approach combining qualitative and quantitative research methods was used. An electronically administered survey was used to obtain the responses of secondary school accounting teachers, while additional insight in the form of semi-structured interviews was obtained from other stakeholders. Although respondents generally agreed that students benefited from accounting as an elective subject at secondary school, all agreed that the development of financial literacy skills was important. Difficulties in introducing a new core subject into an already overcrowded curriculum were acknowledged. However, this difficulty could be overcome by making modifications to the subject “Accounting”. As the most widespread, existing “finance” related subject, Accounting would be the most appropriate vehicle through which to teach financial literacy.
Keywords: Accounting; accounting education; financial literacy; New Zealand secondary schools